Bonde-element i finsk identitet - Kasierska, Katarzyna (Folia Scandinavica Posnaniensia, 2007)
The thesis of the article is that contemporary Finnish national identity has its roots in the nation's agrarism past. The article focuses on several of the most crutcial Finnish identity elements: the Kalevala and folkpoetry in generał as 'national history", naturę love, late migration to cities (1960's and 1970's), hard work as source of esteem, sisu, psychological traits common among Finns, cultural differences between East and West in Finland, gender roles, sauna, and, last but not least, cultural inferiority complex towards 'old European cultures'.